Familial risks of breast cancer - Easton, Douglas F (BioMed Central, 2002)
A recent analysis by the Collaborative Group on Hormonal Factors in Breast Cancer has provided the most precise quantification to date of the familial risks of breast cancer. The familial relative risks are shown to decrease from more than fivefold in women younger than age 40 years with a first-degree relative aged younger than 40 years at diagnosis, to 1.4-fold in women older than 60 years with a relative diagnosed over age 60 years. These risks increase progressively with the number of affected relatives. The risks associated with an affected mother and an affected sister are similar, and the relative (but not absolute) risks are similar in subgroups defined by other established breast cancer risk factors. These results provide a useful basis for counselling of women with a family history of breast cancer, and they have implications for the genetic basis of the disease.